Life Divine in the Theistic Theologies of Hinduism - Ted J Soloman (Journal of Dharma, 1987)
Ramanuja's philosophical theological position is known as Qualified (or modified Non-dualism (Visispiidvaita). This is the view that ultimate reality (the personal God Brahman) is a unity but within the unity there are qualifications or distinctions. God (Brahman) is qualified by the plurality of souls (atmans) and the phenomenal world which together constitute the body (Sarira) of God. There is identity as well as difference between God, the souls, and the world.